If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 2) = 4(x + 8) Reorder the terms: 3(2 + 2x) = 4(x + 8) (2 * 3 + 2x * 3) = 4(x + 8) (6 + 6x) = 4(x + 8) Reorder the terms: 6 + 6x = 4(8 + x) 6 + 6x = (8 * 4 + x * 4) 6 + 6x = (32 + 4x) Solving 6 + 6x = 32 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 6x + -4x = 32 + 4x + -4x Combine like terms: 6x + -4x = 2x 6 + 2x = 32 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 2x = 32 + 0 6 + 2x = 32 Add '-6' to each side of the equation. 6 + -6 + 2x = 32 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 32 + -6 2x = 32 + -6 Combine like terms: 32 + -6 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 14x+2=16+7x | | 2x+13=35-10x | | 2x+.3=.2x+2.1 | | 2x^4-6x^5=12x^2-36x | | 5x-13+11x-61+7x-29=180 | | 64+4x=-1 | | 7=11m-5m | | 4x-x+3=5x+8 | | 16t^2-25=y | | 8(x+4)=174 | | 2(4x+2)=3x+5x+4 | | 5638.92-273.43= | | 8m+6(3)=56 | | 5x+6x+3=7-x | | -16+-7=17 | | (8-4i)+(2+7i)= | | 6x+6=2(x+-1)+2(2x+4) | | 80+2x+20=180 | | -5x=-5.5 | | 12(x+2)=132 | | 36,599.0697=4/3*3.14*r^3 | | 82-6x=7x-17 | | 3x+2=4(2x+1)-5x | | 144+1x=8x+2.5x | | 3c-7(10)=100 | | 7x-2(3+4x)=10 | | 14(-7x)-23=46 | | 80=2x+20 | | (cosx+2)=0 | | 23x-12=-3 | | 4(-2+3y)=40 | | -15+8x=17 |